Ganglion Cyst of the Knee: A Retrospective Review of a Consecutive Case Series - Ivan Bojanić; Damjan Dimnjaković; Tomislav Smoljanović (Acta Clinica Croatica, 2017)
The aim of this study was to describe relevant medical history, clinical symptoms and outcomes in 12 patients having undergone surgical treatment of intra-articular ganglion cysts of the knee at our Department from January 2010 to June 2016. Patient demographics, medical history, knee manifestations, management and outcome were evaluated. The mean patient age was 26.4 (range, 16-46) years. Th ere were seven female and five male patients. Duration of symptoms prior to the operation varied from 2 months to 3 years (mean, 17.1 months). All patients had preoperative magnetic resonance imaging work-up of the knee. Pain was the most common clinical presentation. All patients were surgically treated arthroscopically, and an additional open approach was used in only one of the patients. There were no complications during surgery and the postoperative period was uneventful in all patients. The mean follow up period was 43.5 (range, 9-83) months and no recurrence was observed. All patients remained symptom-free with full range of motion at final follow up. Despite a wide range of intra-articular ganglion cyst presentations and symptoms, our cohort demonstrated an excellent remission rate and functional prognosis following surgical treatment of the ganglion cysts of the knee.